Addressing the Calls for Evidence in Arts and Health: A Quantitative Approach to Understanding the Role of the Arts in the Wellbeing of the Mid West Region of Western Australia - Anwar McHenry, Julia (The Graduate School of Education, The University of Melbourne, 2013)
Despite ambitious claims about the role of the arts in health and wellbeing, and the wealth of quantitative data on the nature of wellbeing, there has been little attempt to quantify the benefits or impacts of the arts using available social indicators. As understanding the role of the arts in the wellbeing of communities is a complex task, this research used a regional case-study to determine a statistical understanding of the relationship between wellbeing and arts engagement, contextualised with existing literature, to capture the uniqueness of the arts experience in a local context. The Mid West region of Western Australia was chosen as the case-study region for its economic and cultural diversity, making this research a distinct shift from a single community case study approach. Data were collected through a household survey measuring self-reported wellbeing and extent of arts engagement. Using backward regression, the final model showed a significant effect for performing arts attendees compared with those who did not attend (V = 0.34, F(3,309) = 3.593, p = 0.014) and arts participants compared with those who did not participate in the arts (V = 0.026, F(3,309) = 2.732, p = 0.044). While there are a number of limitations, this type of analysis is possible and lends support to the complex role of the arts in the wellbeing of the case-study region. The benefits from arts engagement are vast and varied and are both accumulative and a perishable commodity. While further research is required to refine research methods, this research provides some groundwork to further understand the complexity and harness the benefits of the arts for the health and wellbeing of individuals and communities at large.